Dual pathway inhibition as compared to acetylsalicylic acid monotherapy in relation to endothelial function in peripheral artery disease, a phase IV clinical trial - Willems, Loes H.; Thijssen, Dick H. J.; Groh, Laszlo A.; Kooijman, Nina I.; Ten Cate, Hugo; Spronk, Henri M. H.; Donders, A. Rogier T.; van der Vijver-Coppen, Rozemarijn J.; van Hoek, Frank; Nagy, Magdolna; Reijnen, Michel M. P. J.; Warlé, Michiel C. (Frontiers in Cardiovascular Medicine, 2022)
Objective: Dual pathway inhibition (DPI) by combining acetylsalicylic acid (ASA) with low-dose rivaroxaban has been shown to reduce cardiovascular events in patients with peripheral arterial disease (PAD) when compared to ASA monotherapy. A potential explanation is that inhibition of factor Xa improves endothelial function through crosstalk between coagulation and inflammatory pathways, subsequently attenuating the occurrence of cardiovascular events. We hypothesize that the addition of rivaroxaban to ASA in PAD patients leads to improved endothelial function. Design: An investigator-initiated, multicentre trial investigating the effect of DPI on endothelial function. Methods: Patients, diagnosed with PAD, were enrolled in two cohorts: cohort A (Rutherford I-III) and cohort B (Rutherford IV-VI). Participants received ASA monotherapy for a 4-weeks run-in period, followed by 12 weeks of DPI. Macro- and microvascular endothelial dysfunction were studied by measuring carotid artery reactivity upon sympathetic stimulus and by measuring plasma endothelin-1 concentrations, respectively. All measurements were performed during the use of ASA (baseline) and after 12 weeks of DPI. Results: 159 PAD patients (111 cohort A, 48 cohort B) were enrolled. Twenty patients discontinued study drugs early. Carotid artery constriction upon sympathetic stimulation at baseline (ASA) and after 12 weeks of DPI was similar in the total group, 22.0% versus 22.7% (p=1.000), and in the subgroups (Cohort A 22.6% versus 23.7%, p=1.000; cohort B 20.5% versus 20.5%, p=1.000), respectively. The mean concentration of plasma endothelin-1 at baseline and after 12 weeks of DPI did not differ, 1.70±0.57 pmol/L versus 1.66±0.64 pmol/L (p=.440) in the total group, 1.69±0.59 pmol/L versus 1.62±0.55 pmol/L in cohort A (p=.202), and 1.73±0.53 pmol/L versus 1.77±0.82 pmol/L in cohort B (p=.682), respectively. Conclusion: Macro- and microvascular endothelial dysfunction, as reflected by carotid artery reactivity and plasma endothelin-1 concentrations, are not influenced in PAD patients by addition of low-dose rivaroxaban to ASA monotherapy for 12 weeks. Trial registration: Https://clinicaltrials.gov/ct2/show/NCT04218656.